2019
DOI: 10.5194/esd-10-651-2019
|View full text |Cite
|
Sign up to set email alerts
|

Organization of dust storms and synoptic-scale transport of dust by Kelvin waves

Abstract: Abstract. Based on the large-scale transport of dust driven by the winds parallel to the mountains in the Harmattan, Saudi Arabian, and Bodélé Depression dust storm cases, a detailed study of the generation of Kelvin waves and its possible role in organizing these dust storms and large-scale dust transport was accomplished. For this study, observational and numerical model analyses were done in an in depth manner. For this, MERRA reanalysis data sets; WRF-simulated high-resolution variables; MODIS Aqua and Ter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Western Saharan orography stretching from the Atlas mountains in the north to the Aïr mountains in the south has been linked to atmospheric phenomena relevant to dust emission. Kelvin waves regularly propagate along the barrier of the Atlas mountains, organizing downslope winds and jet adjustment processes responsible for severe dust storms in the Harmattan channel (Pokharel & Kaplan, 2019). A relationship may also exist between the Atlas range and the remote Saharan boundary layer, with ascent over the mountains and compensating descent over the central Sahara (Flamant et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Western Saharan orography stretching from the Atlas mountains in the north to the Aïr mountains in the south has been linked to atmospheric phenomena relevant to dust emission. Kelvin waves regularly propagate along the barrier of the Atlas mountains, organizing downslope winds and jet adjustment processes responsible for severe dust storms in the Harmattan channel (Pokharel & Kaplan, 2019). A relationship may also exist between the Atlas range and the remote Saharan boundary layer, with ascent over the mountains and compensating descent over the central Sahara (Flamant et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been stated that the capability of the wind to deflate the dust particles (erosivity), the soil's susceptibility to entrainment (erodibility), and the supply of erodible sediment are three major controlling factors on the dust emission process [8]. It is found that the downslope winds and the unbalanced adjustment processes in the lee of the mountain ranges are the terrain-induced wind storms that also lift the dust from the surface, and produce larger-scale dust aerosol mobilization, and transport [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%